Globalisation, Harmonisation - the Impact on Corporate Income Tax - Gałuszka, Jolanta (Trendy w polityce podatkowej na świecie, 2010)
This paper examines the impact of two important ongoing developments: globalization and harmonization. The main conclusions are that: globalization and harmonisation have the potential to raise economic growth and improve the overall fiscal position, but on the other hand they put pressure on government finances including tax system. Globalization and international factor mobility have implications for efficient taxation of firms and individual taxpayers operating in multiple tax jurisdictions. In such a case we can talk about the impact of globalization in the aspect of tax competition. The question is about harmonization which includes 27 different tax jurisdictions by European Union Directives implementing commom market ruls.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 43-54
Keywords: corporate tax burden; mobility of corporation; race-to-the-bottom; favourable tax regime